Inovasi e-Layanan Kepustakaan di Perpustakaan Lembaga Riset Studi Kasus pada Pusat Data dan Dokumentasi Ilmiah - Rahmadani Ningsih Maha; Nur Rizzal Rosiyan (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2021)
Library service innovation is part of realizing the excellent service of the library.The pandemic period that occurred from March 2020 to mid-2021 made the Library Of Data and Scientific Documentation Center of the Indonesian Institute of Sciences strive to innovate e-library services.The innovations carried out by the Data and Scientific Documentation Center Indonesian Institute of Sciences Library include innovations of its service types, revision and addition of ISO Library Services (SOP) & risk management, and Regional Service Systems integrated in INTRA LIPI.The research method used is through observation and study of literature. The purpose of this writing is to inform the innovation of PDDI LIPI's e-service literature including the type of service, revision and addition of ISO Library Services (SOP) & risk management and Regional Service System integrated in INTRA LIPI and challenges must be faced so that this innovation can be realized.